Analysis of Self-Confidence in the Use of the English Language - Hidayatul Faridah; Alifa Suri Rahmadhina; Muhamad Solih (Glosains: Jurnal Sains Global Indonesia, 2024)
This study explores the self-confidence of education professionals in using English in Cipicung District, Kuningan, West Java. Employing a qualitative descriptive method, the research involved 40 participants selected through purposive sampling. Data were collected via structured interviews based on four indicators: belief in one’s abilities, independent decision-making, positive self-concept, and assertiveness. The findings reveal that most participants have low speaking skills and limited vocabulary, leading to hesitation, anxiety, and a tendency toward passive communication. While listening and writing abilities were relatively stronger, speaking in English remained a major challenge. Environmental factors, lack of supportive practice opportunities, and criticism over pronunciation and word choice further affected confidence levels. Nevertheless, many participants maintain strong motivation to improve, engaging in informal strategies such as watching English films, listening to music, and using vocabulary-learning applications. The study emphasizes the need for supportive environments and consistent speaking practice to foster self-confidence and enhance English communication skills among educators and educational staff.